Promoting Multi Literacy Pedagogy in Teaching Reading in Indonesian Higher Education - Khaerati Syam, Ummi (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is one of the countries where students have a low reading interest. Therefore, teaching reading in universities needs an appropriate strategy to engage students’ attention in learning reading to achieve high interest in reading. Multi-literacy pedagogy is a multimodal way of communication that includes technology and multimedia in teaching so that it offers a new classroom pedagogy that extends and helps manage classrooms. This study aimed at finding out how the Indonesian lecturers apply their understandings and experiences with multi-literacy pedagogy in their classroom teaching, particularly in teaching reading. The data were obtained by distributing an open-ended questionnaire to 20 Reading lecturers who were selected randomly from a population of 100 at Muhammadiyah universities in Makassar, Indonesia. The result of the data analysis showed that the Reading lecturers applied their understandings and experiences with multi literacy pedagogy in the form of: 1) situated practice by encouraging and motivating students to discuss and share ideas about the lessons within a small group of students in the classroom; 2) overt instruction with which the lecturers suggest the students to use ‘graphical concept map features’ for creating an interactive concept-map of their classroom learning; 3) critical framing in which the lecturers encourage students to notice and analyze practices of communicating meaningful ideas in schools and groups; and 4) transformed practice where the teachers encourage students to connect their learning experiences with their daily classroom lessons.